2017
DOI: 10.1556/446.13.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of water-yield basil function under deficit irrigation conditions and use of nano fertilizer

Abstract: Basil (Ocimum basilicum L.) is one of the important aromatic plants belonging to the family Lamiaceae, which is used as an herb, spice as well as fresh vegetable.The present study was performed to determine the irrigation depth index under different management conditions with evaluating the effect of deficit irrigation, soil texture and nano fertilization on basil. The experiment was performed as a factorial based on randomized complete block design (RCBD) with 18 treatments and three replications at weather s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These lower values for evapotranspiration may be attributed to the shorter cultivation period (34 days vs. 71 days) and the location (Belgium vs. Colombia). Nevertheless, the measured values for ET agree sufficiently with the findings reported by other researchers to validate our findings and calculations (Daza-Torres et al, 2017;Naderianfar et al, 2017). Irrigation frequency, timing and duration were identical in '19°C', '23°C' and '25°C' treatments, while the water use over the cultivation period was different.…”
Section: °C 23°c 25°csupporting
confidence: 92%
“…These lower values for evapotranspiration may be attributed to the shorter cultivation period (34 days vs. 71 days) and the location (Belgium vs. Colombia). Nevertheless, the measured values for ET agree sufficiently with the findings reported by other researchers to validate our findings and calculations (Daza-Torres et al, 2017;Naderianfar et al, 2017). Irrigation frequency, timing and duration were identical in '19°C', '23°C' and '25°C' treatments, while the water use over the cultivation period was different.…”
Section: °C 23°c 25°csupporting
confidence: 92%
“…Note that the EUE, expressed as g FW kW −1 , is defined as the ratio of the fresh mass of the sweet basil plant and the electricity consumption of LEDs, and the WUE, expressed in g FW L −1 H 2 O, is defined as the ratio between the leaf fresh mass and the volume of water used. Generally, WUE increases the plant’s fresh mass [ 35 ] and fruit yield [ 36 ]. During the experiments, the air temperature (T air in °C) and relative humidity (RH%) inside each tent were measured using a thermometer (Green May International Ltd, Shenzhen, China), and data were manually logged on every day at 8:00 pm.…”
Section: Methodsmentioning
confidence: 99%
“…Results showed by using optimum water depth in water limiting condition, water use was decreased by 36% and water productivity and net income per unit of water use was increased by 42% and 23%. Economic assessment of deficit irrigation and its effect on yield and water use efficiency of Basil was conducted by English 1990 method (Naderianfar et al, 2017). Optimization of production, cost and income functions showed that 25% decrease in water use caused maximum water use efficiency and led to the maximum net income per unit of water.…”
Section: Introductionmentioning
confidence: 99%